Model Pembelajaran Organizing Event dan MICE berbasis Project Based Learning di Jurusan Pariwisata, Politeknik Negeri Bali - Trisnayoni, Raden Ayu; Harmini, A.A. Ayu Ngurah; Ary Susyarini, Ni Putu Wiwiek; Dewi, Ni Wayan Sintya (Jurnal Ilmiah Pariwisata, 2023)
The purpose of this study is to create a learning model with Project Based Learning for event organizing and MICE courses at the Department of Tourism, Bali State Polytechnic. In making this model, researchers have collected data by observation, interview and case study methods in 2 (two) Event Organizer companies in Bali. The research method uses qualitative analysis with NVivo 12 plus software to help researchers code (code data) and display (present data) with project maps. The result of this study is a better teaching method model with Project Based Learning for the Organizing Event &; MICE course. This model includes a Project Based Learning component and can be implemented for students of the Department of Tourism at the Bali State Polytechnic. With the Project Based Learning learning model, it is hoped that students will better understand the organization of events & MICE in accordance with the event industry. Keywords: Learning Model, Project-Based Learning, Event Organizing & MICE, Department of Tourism